Heart failure in diabetes: From an increased risk to a treatment target - Eberhard Standl (Сахарный диабет)
Heart failure (HF) is one of the most common comorbidities of type 2 diabetes mellitus (T2DM) and poor glycaemic control can worsen the HF outcomes and increase the risk of hospitalisations. With the entry of several antihyperglycaemic agents for the management of T2DM over the last decade, there has been an increasing concern regarding the cardiovascular (CV) safety profile of these agents. In view of this, FDA mandated the demonstration of cardiovascular risk-benefit profile of these agents through specifically designed CV outcome trials. Although we have several findings from these trials, none of them included HF as a primary endpoint indicating the need of trials focusing on HF. Here, we briefly discuss the results of the CV outcome trials in the context of HF.